Dominant Actors at Online News Portals in Cases of Policy Changes - Tsany Raihan, Sheila Anindya; Prianti, Desi Dwi (UPT Publikasi Ilmiah UNISBA, 2024)
The media has contributed significantly to the polemic regarding the age limit of prospective presidential candidates in Indonesia. To answer how the media contributes to this polemic, this study applies discourse network (DNA) analysis. By looking at three leading online media outlets in Indonesia, Viva.co.id, Tempo.co Dan Mediaindonesia.com in October 2023-January 2024, this study argues that the discrepancy around the age limit of presidential candidates not only affects the way the public views the issue but also exposes the public to the issue of transparency of the highest constitutional institution in Indonesia (MK). Moreover, by applying the Discourse Coalition Framework (DCF), this study found that Mediaindonesia.com and Tempo.co have the same views regarding the issue of age restrictions, which are harmful to the Constitutional Court’s policies. Meanwhile, Viva is relatively supportive and agrees with the policy. Media organizations use influential individuals to build discourse as part of the narrative. They use these people as their source to support certain discourses. These people range from academics, activists, and political parties to speaking experts to experts.